THE ACTIONS OF A.M.A PROJECT - ADAPTED MOTOR ACTIVITY - AND THE CHARACTERISTICS OF DISABILITIES PARTICIPANTS - Aline Miranda Strapasson; Jalusa Andréia Storch; Dcheimy Janayna Baessa (Universidade Estadual do Oeste do Paraná, 2014)
The present study aimed to characterize the participants A.M.A Project - Adapted Motor Activity. Through field research, we interviewed 88 participants with disabilities A.M.A Project. The instrument used was a questionnaire. The results stated that 35% of participants have a physical disability, and the water activities practiced by 47%. The reasons mentioned for membership in the project was primarily the desire to perform physical activities, since the benefits relate to improved quality of life. It is understood that extension projects are the spaces for the development and construction of new knowledge, which should also include the participation of people with disabilities.